Liposomal doxorubicin: a phase II trial - Balbi, G.; Visconti, S.; Monteverde, et al., A. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim of the work: In patients with disseminated endometrial carcinoma, doxorubicin is used as a single agent or in combination therapy.We have carried out a phase II clinical trial of liposomal doxorubicin in first-line therapy of women with disseminated endometrial carcinoma. Methods: Between September 2001 and May 2003, 22 patients with histologically confirmed disseminated endometrial carcinoma, were enrolled in this study. Eleven patients had been previously treated with radiation, none of them had been treated with chemotherapy. Liposomal doxorubicin (40 mg/m2) was intravenously administered at 4 week intervals until toxicity or progression. Results: The most common adverse events were fatigue, anemia, pain, and dermatologic toxicity (EPP). Eight patients (36%) achieved a tumor regression (Complete response, CR 3; Partial response, PR 5), ten (46%) maintained stable disease, and four (18%) experienced increasing disease. Conclusion: Liposomal doxorubicin has a lower cardiologic toxicity than doxorubicin with a similar response rate in patients with disseminated endometrial carcinoma.